Case report: Intraventricular tumor removal using transcallosal approach and follow-up in three dogs - Lehner, László; Czeibert, Kálmán; Csébi, Péter; Diószegi, Kristóf; Nagy, Gábor (Frontiers in Veterinary Science, 2023)
This case series describes the surgical removal of lateral ventricular tumors using a transcallosal approach, long-term follow-up, and magnetic resonance imaging (MRI) results of 3 dogs. Two tumors were benign choroid plexus tumors (CPT). One was a grade 2 astrocytoma. Complete tumor removal was achieved using the transcallosal approach. All dogs had ventriculomegaly which remained static or progressed during the follow-up period. All dogs had epileptic seizures before the surgical procedure which persisted despite tumor removal. One dog with CPT was alive after 3 years and 5 months and had minor focal seizures every 3-4 months. No other clinical signs were observed. The second dog with CPT was neurologically free for 17 months after the surgical procedure but died due to acuteonset therapy-resistant generalized epileptic seizures. The third dog with intraventricular astrocytoma experienced epileptic seizures 2 and 4 months after the surgical procedure. The second event was therapy-resistant which led to death.